Occurrence of Macrophomina phaseolina on Chickpea in Italy: Pathogen Identification and Characterization - Eliana Dell’Olmo; Pasquale Tripodi; Massimo Zaccardelli; Loredana Sigillo (Pathogens, 2022)
Climate change has led to the spread of plant pathogens in novel environments, causing dramatic crop losses and economic damage. Botryosphaeriaceae represents a massive fungal family, containing a huge number of plant pathogens, which are able to infect several hosts. Among them, Macrophomina phaseolina is a necrotrophic fungus, responsible for several plant diseases, including the soft stem rot of common bean, crown rot on strawberry and charcoal rot of several legumes. Here, Macrophomina, causing crown charcoal rot in chickpeas, was isolated from symptomatic plants in Cicerale (SA), Campania, South Italy. Morphological and molecular characterization was carried out and pathogenicity tests were performed. Phylogenetic analyses were performed comparing Macrophomina strains coming from different geographic areas and hosts. The experiments confirmed the pathogenicity of the isolate CREA OF 189.2 on chickpea, while host range highlighted the polyphagous nature of this strain; thus, symptoms were reported on lentils, common bean and cantaloupe. The multidisciplinary approach allows us to increase the knowledge about this emerging pathogen. To the best of our knowledge, this is the first report on Macrophomina phaseolina from chickpeas in Italy.